On growth of the inverse semigroup of partially defined co–finite automorphisms of integers - Bezushchak, O. (Algebra and Discrete Mathematics, 2004)
The inverse semigroup of partially defined co– finite automorphisms of integers is considered. This semigroup is presented by generators and defining relations and its growth function is described.